2010
DOI: 10.1103/physrevlett.104.157403
|View full text |Cite
|
Sign up to set email alerts
|

Challenge to the Charging Model of Semiconductor-Nanocrystal Fluorescence Intermittency from Off-State Quantum Yields and Multiexciton Blinking

Abstract: Semiconductor nanocrystals emit light intermittently; i.e., they “blink,” under steady illumination. The dark periods have been widely assumed to be due to photoluminescence (PL) quenching by an Auger-like process involving a single additional charge present in the nanocrystal. Our results challenge this long-standing assumption. Close examination of exciton PL intensity time traces of single CdSe(CdZnS) core (shell) nanocrystals reveals that the dark state PL quantum yield can be 10 times less than the biexci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
238
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(258 citation statements)
references
References 39 publications
20
238
0
Order By: Relevance
“…As an extension of this framework, multiply charged states were suggested in order to account for a dark-state quantum yield much lower than its biexcitonic counterpart. 29 Multiply charged states are also consistent with the distribution of lifetimes in the dark state 38 as well as the present findings on the distribution of dark intensity states. The wide distribution of bright intensity states reported in this paper could be due to an alternative mechanism of fluctuating non-radiative channels.…”
Section: Implications Of the Distributed States On Models Of Blinkingsupporting
confidence: 77%
See 1 more Smart Citation
“…As an extension of this framework, multiply charged states were suggested in order to account for a dark-state quantum yield much lower than its biexcitonic counterpart. 29 Multiply charged states are also consistent with the distribution of lifetimes in the dark state 38 as well as the present findings on the distribution of dark intensity states. The wide distribution of bright intensity states reported in this paper could be due to an alternative mechanism of fluctuating non-radiative channels.…”
Section: Implications Of the Distributed States On Models Of Blinkingsupporting
confidence: 77%
“…Unbiased estimations could be subtracted by considering the peaks within the intensity histogram rather than looking at counts from individual bins. 29 For example, the dark intensity fitted to the trajectory in Fig. 2 could be anywhere in the 0-4 counts/10 ms range, depending on background noise.…”
Section: Discussion and Comparison With Experimentsmentioning
confidence: 99%
“…Furthermore, we have shown that both trion charge states and concomitantly their charged biexcitons have high luminescence quantum yields, contrary to observations at room temperature 25 , indicating that Auger recombination is inefficient in these materials. Thus the photo-charging mechanism of our NCs can be attributed to a tunnelling process, which has significant implications for alternative photoluminescenceblinking mechanisms 41,42 . Another interesting consequence of NC engineering is revealed in the g-factor measurements.…”
Section: Discussionmentioning
confidence: 99%
“…However, charging of NCs can promote Auger recombination and trap states can bind charge Colloidal lead halide perovskite nanocrystals H Huang et al carriers, preventing recombination, all of which has been considered to contribute to blinking. [102][103][104] Tian et al 98 observed PL blinking from MAPbI 3 nanorods (Figures 8h-j) and attributed it to photo-induced activation and de-activation of PL quenching sites, presumably present at the ends of the rods where formation of geometrical and chemical defects are most likely to occur. Similarly, blinking was also observed in single perovskite MAPbBr 3 NCs and attributed to the presence of charge trapping surface states.…”
Section: Quantum Confinement In Perovskite Ncsmentioning
confidence: 99%